2008
DOI: 10.1097/qai.0b013e3181831806
|View full text |Cite
|
Sign up to set email alerts
|

HIV Among African-Born Persons in the United States: A Hidden Epidemic?

Abstract: In some areas, classifying HIV cases among foreign-born blacks as occurring in African Americans dramatically alters the epidemiological picture of HIV. Country of birth should be consistently included in local and national analyses of HIV surveillance data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
62
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 6 publications
4
62
0
Order By: Relevance
“…9 In a study evaluating aggregate data in eight states (California, Georgia, Massachusetts, Minnesota, New Jersey, Washington State, New York, and Virginia/ Washington, D.C.) from 2003 to 2004, African-born individuals accounted for up to 49.8% of HIV diagnoses in black individuals (mean, 8.0%; range, 2-50%). 10 HIV testing is the first entry way into vital care and treatment services. Concurrent diagnosis of HIV and AIDS or obtaining a diagnosis of AIDS in close proximity to an initial diagnosis of HIV is usually attributed to late testing.…”
mentioning
confidence: 99%
“…9 In a study evaluating aggregate data in eight states (California, Georgia, Massachusetts, Minnesota, New Jersey, Washington State, New York, and Virginia/ Washington, D.C.) from 2003 to 2004, African-born individuals accounted for up to 49.8% of HIV diagnoses in black individuals (mean, 8.0%; range, 2-50%). 10 HIV testing is the first entry way into vital care and treatment services. Concurrent diagnosis of HIV and AIDS or obtaining a diagnosis of AIDS in close proximity to an initial diagnosis of HIV is usually attributed to late testing.…”
mentioning
confidence: 99%
“…While immigrants as a group comprised about 13 % of the U.S. population, from 2007 to 2010, 16 % of people diagnosed with HIV were born outside the U.S. [2]. In a study in eight jurisdictions in the U.S., African-born persons were .6 % of the total population, however, accounted for 3.8 % HIV prevalence, although the rates highly varied among the sites [3]. In Minnesota, for instance, the African-born population was 1 % of the state's population, but accounted for 13 % of new HIV diagnosis in 2012 [4].…”
Section: Introductionmentioning
confidence: 91%
“…During the same period, in the state of Minnesota, among 1047 African-born persons living with HIV 98 (9 %) and 234 (22 %) were immigrants from Somalia and Ethiopia, respectively [7]. Overall, African-born persons living in the U.S. are disproportionately affected by HIV epidemic [3][4][5][6][7]. The epidemiological dynamics of HIV epidemic among Africanborn immigrants in the U.S. is characterized by higher rates of HIV diagnosis-most affected are African-born black women, predominately heterosexual transmission, and late stage of diagnosis [2,4,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Akinsete et al 9 reported an increase from 4% in 1996 to 16% in 2005 in the percentage of newly diagnosed HIV-infected persons who are African-born in Minnesota; approximately one fifth were refugees admitted through the U.S. waiver program and the majority were diagnosed at an immigration examination. Kerani et al 10 looked at the rates of HIV diagnoses in Africanborn persons in areas of the United States with larger Africanborn immigrant populations. Overall, the African-born population was reported as only 0.6% of the total population and yet accounted for 3.8% of HIV diagnoses.…”
mentioning
confidence: 99%
“…While the proportion of HIV-infected persons who were African-born varied from 1.3% in California to 20.2% in Minnesota, the burden of HIV in African-born was significantly disproportionate to the size of the African-born population within each area studied. 10 Johnson et al 11 conducted a broader evaluation of CDC data in foreign-born blacks from 33 states reporting HIV infections from 2001 to 2007. While their data show a decrease in HIV rates in both foreign-born and U.S.-born blacks, it was much less of a decrease in the foreign-born population.…”
mentioning
confidence: 99%